MENGUKUR EFISIENSI INTERMEDIASI SEBELAS BANK TERBESAR INDONESIA DENGAN PENDEKATAN DATA ENVELOPMENT ANALYSIS (DEA) - Kurnia, Akhmad Syakir (JURNAL BISNIS STRATEGI, 2004)
Bank Efficiency has been an important issue in the process of Indonesia's banking recovery after facing banking crisis. In most of the transition countries such Indonesia the relative comparison of banks by size, type of ownership has at some point been an issue. How good it is to let new banks enter the market? Should the state owned banks be sold to public or foreigners? Do small banks have future in the era of globalization? How good the intermediation function has been done by banks? These, and other questionscontinue to dominate discussions of Indonesia 's banking sector. In this paper I analyze efficiency of eleven largest banks in Indonesia using Data Envelopment Analysis (DEA). DEA is a methodology for analyzing relativeefficiency and managerial performance of productive units having same multiple inputs and multiple outputs. It allows us to compare relative efficiency of banks by determining the efficient banks, which span the frontier. The most important advantage of DEA over traditional econometric frontier studies is that it is a non parametric, deterministic method and therefore doses not require a priori assumptions about the analytical form of the production function. Therefore the probability of misspecification of the production technology is zero. The disadvantage is that, being a non parametric method, it is more sensitive to possible mismeasurement problems.I measured relative efficiency of eleven largest banks in Indonesia according to their size and type of ownership. Eleven largest banks in Indonesia dominate over 60% of banking sector. I found that in 2002, no state owned banks reached efficient, three of six largest private owned banks reached efficient frontier and Citibank as one and only foreign owned banks reached efficient. In 2003, only one of four state owned bank reached efficient. Three of six private owned banks reached efficient. Citibank still reached efficient. Based on this result, type of ownership appears to have correlation with efficiency. Foreign owned bank is the most efficient, and that state owned banks are the less efficient. Private owned banks are in the middle. Only fifty percent of private owned banks reached efficient.